Numerical simulation of droplet merging and chemical reaction in a porous medium. (December 2017) - Yu, Hanjun; Son, Gihun; Shim, Woosup
Abstract: The chemical reaction between droplets merging in a porous medium is numerically investigated by solving the conservation equations of mass, momentum and chemical concentration in the internal and external regions of the porous medium. A level-set formulation for two-phase flows is extended to include the effects of porosity and mass transfer with chemical reaction. The numerical result for one-dimensional mass transfer with chemical reaction shows good agreement with the exact solution. The numerical method is applied to investigate the effects of droplet size, impact velocity and porosity on the droplet merging and the associated chemical reaction in a porous medium.